THE EFFECTIVENESS OF DECREASING LEVELS OF CHROMIUM (Cr) USING COAGULANT FeSO4 AND Al2(SO4)3 (Research Study Batik Home Industry in The Village of Tuban Jarorejo Year 2018) - Kurnia Wardhani; Ferry Kriswandana; Pratiwi Hermiyanti (Poltekkes Kemenkes Surabaya, 2018)
Liquid waste from the results of the process coloring or dyeing have thick, colored characteristics of pH, concentration of Biological Oxygen Demand (BOD) height and color substance in which there is heavy metal content of chromium that is alleged to be toxic. One effort to decrease it is by the process of coagulation with coagulant FeSO4 and Al2(SO4)3. This research aims to kniw the effectiveness of Cr levels decrease total between coagulant FeSO4 and Al2(SO4).This type of research is experimental with Pretest-Posttest with Control Group design research. Sample required as many as 27 samples with replication nine times for each coagulant. Analysis of data used to use multivariate anova test for the purpose of knowing the difference 2 treatment groups. Percetage of chromium levels decrease after coagulation using coagulants FeSO4 and Al2(SO4)3with their respective dose variation 20 gr/l, 30 gr/l and coagulant Al2(SO4)3with coagulantdose variation 20 gr/l, 30 gr/l in row amounted to 75,89%; 83,00%; 71,40%; 91,76%. The most effective results in decreased levels of Cr in waste liquid of batik is 91,76% with coagulant Al2(SO4)3 dose variation 30%. On the results of statistics produces the value of p 0,05 is 0,000 the H0is rejected, which means that there is a difference in total Cr levels using coagulant FeSO4 with coagulant Al2(SO4)3.Based on the precentage of the total Cr levels decrease, effective coagulant to lower levels of total Cr in batik liquid waste is to use a coagulant Al2(SO4)3 with dose 30 gr/l. Advice for owners batik home industry by making waste watern treatment installations to process liquid waste it generates, which there is a processing unit with coagulation method that uses Al2(SO4)3coagulantto lower levels of chromium in sewage. Key words: Chromium (Cr), Coagulant, The liquid waste of batik